The Strategy of the Generasi Impian Medan Organization as an Alternative Learning Space to Improve Community Literacy - Anindia Larasati; Yusniah Yusniah (FKIP - Universitas Riau, 2026)
Public literacy levels in Indonesia remain relatively low due to limited access to reading materials, a lack of enthusiasm for reading, and a scarcity of sustainable literacy initiatives. This study aims to identify the implementation of the Medan Generasi Impian literacy program, analyze its organizational strategies as an alternative learning space for improving public literacy, and examine the elements that facilitate or hinder the program. A descriptive qualitative case study design was employed. Data collection involved participant observation, semi-structured interviews, and document analysis, with two key informants selected via purposive sampling. The Miles and Huberman interactive model was used to analyze the data, and source triangulation was utilized to validate the findings. The results indicate that Medan Generasi Impian employs age-appropriate reading materials, mentoring, educational games, collaborative reading, and role-playing exercises to implement learner-centered literacy practices. Participants' reading interest, literacy skills, willingness to learn, communication skills, and self-confidence all improved as a result of these strategies. The findings suggest that while Medan Generasi Impian has successfully served as an alternative learning environment, sustaining the literacy program remains challenging due to a lack of funding, educational facilities, volunteers, and reading enthusiasm.